The European Union Deforestation Regulation: Impacts on the Coffee Exporting Activities of Vietnam - Phuong Thao, Dong (VNU Journal of Science: Legal Studies; Vol 41 No 3DO - 10.25073/2588-1167/vnuls.4695, 2025)
Adopted in April 2023, the European Union Deforestation Regulation (EUDR) imposes an import ban on agricultural commodities associated with deforestation activities, including coffee. Accordingly, for Vietnam, the coffee export sector may be significantly affected, as coffee currently represents the agricultural commodity with the highest export value to the European Union. Acknowledging the urgency of this issue, this study first provides an in-depth analysis of the provisions of the EUDR, thereby offering assessments of the challenges and opportunities for Vietnam’s coffee sector in exporting to the European Union market under the impact of the EUDR, based on an analysis of production and export conditions. Subsequently, the paper highlights certain positive aspects that the EUDR may bring, and some primary challenges to the export of coffee in particular and agricultural products in general to European Union, including challenges related to traceability, financial capacity, and competitiveness. Finally, the study proposes several macro- and micro-level solutions to address these challenges. In general, the study contributes to supporting Vietnamese export enterprises in adapting to the EUDR and inspires public policymakers to establish appropriate mechanisms to ensure the effectiveness of Vietnam’s coffee exports to the European Union in light of the EUDR’s official entry into force on 30 December 2024.